Proceedings of the Proceedings of the 1st International Multi-Disciplinary Conference Theme: Sustainable Development and Smart 2020
DOI: 10.4108/eai.28-6-2020.2297934
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical Multilevel Inverter with Modified Absolute Sinusoidal PWM Technique for Sensorless Control of Induction Motor

Abstract: Sensorless speed and torque control of a three-phase induction motor utilizing cascaded H-bridge inverter with unequal selected DC voltage sources (USDCVS) is presented in this study. Several output voltages with minimum distortions and IGBTs are achieved with DC input voltage sources equal to (1, 3, 9) Vdc. The induction motor speed and torque are estimated depending on the instantaneous output phase voltages and currents of the drive circuit. A novel controller circuit is built depending on a modified absolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…[ [39][40][41][42][43][44][45][46][47] • Minimization of transmission line loss. • The enhancement of transmittable power.…”
Section: • Loss Reductionmentioning
confidence: 99%
“…[ [39][40][41][42][43][44][45][46][47] • Minimization of transmission line loss. • The enhancement of transmittable power.…”
Section: • Loss Reductionmentioning
confidence: 99%
“…The THD value of the 9-level output was 9.5% with zero-level and 12.5% with absence zero-level. In 2020 [15], the same power and control circuits suggested by [10] built with sensor less speed/torque control of an induction motor at different operation conditions. The suggested circuit provided good response and quality.…”
Section: Introductionmentioning
confidence: 99%
“…The lowest distortion value of the output waveform at 1kHz is 6.71%, while with 2kHz is 6.59%. In 2020 ANTAR et al [22], the same power and control circuits suggested by [16] used for sensorless speed and torque control of an induction motor at different operating conditions. The system gave good response and quality.…”
Section: Introductionmentioning
confidence: 99%